Cluster protocols in SCIT: enough evidence for practical use? - Pfaar, Oliver; Leitzbach, Sarah; Hörmann, Karl; Klimek, Ludger (Current opinion in allergy and clinical immunology, 2010)
Purpose of review - The review provides a comprehensive evaluation of Cluster schedules in subcutaneous-specific immunotherapy (SCIT) in terms of the safety profile and onset of clinical and immunological effects. - Recent findings - Recent major clinical studies could clearly reveal that Cluster schedules with both (semi-)depot-allergen preparations and chemically modified allergen preparations (‘allergoids’) are well tolerated therapeutic options in SCIT comparable to the safety profile of conventional build-up schedules. Moreover, preliminary data indicate that these accelerated protocols result in a more rapid achievement of clinical and immunological effects. - Summary - Conventional schedules in SCIT have the disadvantage of both a high expenditure of time and the need for a high patient compliance. In accelerated cluster schedules two to three injections are administered sequentially per treatment day (with an interval of 30 min between the injections) in weekly intervals aimed to reach the maintenance dose of SCIT in a short time interval. Recent studies indicate that these accelerated SCIT protocols result in a more rapid achievement of clinical and immunological effects than conventional schedules. Moreover, the safety profile is comparable between conventional and cluster SCIT.
Gesehen am 28.03.2023